Respon Mahasiswa Terhadap Metode E-Learning Ditinjau Dari Keefektifan Metode Pembelajaran - Shofiyana Ramdani; Meliyasa Khorina Laili; Nur Fajrie; Sekar Dwi Ardianti (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2024)
This study aims to determine student responses to the E-Learning method in terms of the effectiveness of the learning method. The method used in this study is a quantitative method with survey research. The data collection technique was carried out by giving a questionnaire in the form of a Google form where the results will be presented in tabular form. Respondents were taken from 60 samples representing students of the 2021 Elementary School Teacher Education study program from Muria Kudus University who used E-Learning in the world of lectures. The stages of data processing are carried out by presenting data and analyzing data in a descriptive form to be able to draw conclusions. The research results were obtained by using several indicators and the highest scores were: (1) students' breadth in using E-Learning 63.9%; (2) student acceptance of E-Learning facilities 55%; (3) effectiveness of using E-Learning 55.6%.